Integrated PjBL-STEM in Scientific Literacy and Environment Attitude for Elementary School - WINARNI, Endang Widi; KARPUDEWAN, Mageswary; KARYADI, Bhakti; GUMONO, Gumono (Asian Journal of Education and Training, 2022)
Integrating Project-Based Learning (PjBL) and Science, Technology, Engineering, and Mathematics (STEM) in elementary schools can increase the quality of human resources in industrialization and globalization to maintain the environmental system and fulfill 21st century competencies. The research method used Quasi-Experiment from elementary schools in Bengkulu, Indonesia, with 50 respondents for the experiment and control class. For all attitude, context, and knowledge indicators, the data was analyzed using a non-parametric test and an ANOVA. The instrument’s validity was tested statistically and by experts. The results show that PjBL and STEM significantly affect scientific literacy and environmental attitudes in three indicators. Furthermore, the diorama project with PjBL and STEM allows students to investigate environmental conservation efforts, accommodate science and technology. Students’ success in making slogans to solve science problems. Environmental literacy instruments and STEM are suggested to be integrated with cognitive, motivation, behavior, and values.